Respuesta :

Answer:

Step-by-step explanation:

Using long division:

                        13x^2 + 13x + 15   <------------Quotient

                       _________________________

2x^2 - 3x - 5 )  26x^4 - 13x^3 -  74x^2 - 46x - 24

                        26x^4 - 39x^3 - 65x^2

                                     26x^3 -   9x^2  - 46x

                                     26x^3 -  39x^2 - 65x

                                                    30x^2 + 19x   - 24

                                                    30x^2  - 45x  - 75

                                                                   64x + 51  <---- Remainder.     Division algorithm:

a = bq + r

Here a = the original expression , b = the divisor (2x^2 - 3x - 5), q is the quotient and r = the remainder,

26x^4 - 13x^3 - 74x^2 - 46x - 24 = (2x^2 - 3x - 5)(13x^2 + 13x + 15) + 64x + 51

= 2x^2(13x^2 + 13x + 15) - 3x(13x^2 + 13x + 15) - 5(13x^2 + 13x + 15) + 64x + 51

= 26x^4 + 26x^3 + 30x^2 - 39x^3 - 39x^2 - 45x - 65x^2 - 65x - 75+64x+51

= 25x^4 - 13x^3 - 74x^2 - 46x - 24 which is the same as the above.